Mapeamento de QTLs associados à resistência a Alternaria alternata em híbridos de citros - Campos, Kelly Aparecida Fernandes de (Universidade Federal de São Carlos, 2016)
Alternaria brown spot (ABS) disease is caused by a fungus of Alternaria genus, that causes injury and fruit depreciation, leaves fall, drought of pointers and new shoots. The action of the fungus Alternaria alternata f. sp. citri is directly associated by the presence of toxin receptors on susceptible genotypes. The objectives of this study were: (1) to characterize the phenotype of 264 citrus hybrids obtained from crossing LPA Pera de Abril sweet orange (Citrus sinensis L. Osbeck) vs H163, a hybrid between Murcott tangor (C. reticulata x C. sinensis) x Pera sweet orange (C. sinensis), for response to A. alternata, via conidia suspension inoculation of detached young leaves (in vitro) and (2) construction of a linkage map using DArT_seq markers to identify possible QTL (Quantitative Trait Loci) associated to disease resistance. The fungus was isolated from lesions of Murcott tangor fruits with ABS symptoms and inoculated via conidia suspension on detached young leaves (in vitro). Two hundred and thirty five hybrids were evaluated and 70 (30%) showed different levels of disease symptoms after 72 hours of inoculation with the fungus on detached leaves and 165 (70%) were asymptomatic. The integrated linkage map, built with OneMap program, resulted in 726 DArT_seqTM and three SSR molecular markers that covered nine linkage groups, corresponding to the haploid number of chromosomes of the specie. Using the values of AUDPC, seven QTLs associated with resistance to ABS were localized in linkage groups of the integrated map. The integrated linkage map of Pera de Abril sweet orange (LPA) vs. H163 has a high degree of synteny with pseudo-chromosomes of sweet orange (C. sinensis).
QTL mapping associated with resistance to Alternaria alternata in citrus hybrids
Keywords: Citros; Tangerina; Laranja; Mancha marrom de alternaria; Citrus; Mandarin; Orange; Alternaria brown spot; CIENCIAS AGRARIAS